2023
DOI: 10.1108/neje-07-2022-0046
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the model of social entrepreneurial intention: the role of perceived financial security

Abstract: PurposeAlthough few studies indicate that financial concerns matter to social entrepreneurs, the literature is unclear about the extent to which a financial motive affects the intention to start a new social enterprise. Moreover, prior research suggests that the intention to start a new enterprise heavily depends on the societal context in which the enterprise operates. Therefore, this study aims to examine the seminal model of social entrepreneurial intention (SEI) developed by Hockerts (2017) in a different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…For example, Kruse (2020) and Politis et al (2016) found that two of the TPB antecedents, attitude towards social entrepreneurship and perceived behavioural control, influence SEI. However, studies that applied Hockerts’ (2017) model found empathy and moral obligation as less influential antecedents of SEI in different social contexts (Aure, 2018; De Sousa-Filho et al , 2020; Lacap et al , 2018; Ukil et al ., 2023).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…For example, Kruse (2020) and Politis et al (2016) found that two of the TPB antecedents, attitude towards social entrepreneurship and perceived behavioural control, influence SEI. However, studies that applied Hockerts’ (2017) model found empathy and moral obligation as less influential antecedents of SEI in different social contexts (Aure, 2018; De Sousa-Filho et al , 2020; Lacap et al , 2018; Ukil et al ., 2023).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This concept serves as a mediator that connects social entrepreneurial role models to social entrepreneurial intent, implying that the impact of social entrepreneurial role models on social entrepreneurial intent is channeled through the lens of self-efficacy. Recent research by Ukil et al (2023) and Ukil (2022) has specifically explored the mediating role of social entrepreneurial self-efficacy within the domain of social entrepreneurship. Their findings indicate that social entrepreneurial selfefficacy acts as a mediating factor between exposure to social entrepreneurial role models, prior experience in social entrepreneurship and the intent to engage in social entrepreneurial activities.…”
Section: The Mediating Role Of Social Entrepreneurial Self-efficacymentioning
confidence: 99%
“…Collaboration and network-building emerge as crucial elements in mitigating risks, as partnerships with other organizations and stakeholders provide additional resources and support [30], [31]. Effective risk management in social entrepreneurship extends beyond risk-taking to include resilience and adaptability [32]. Entrepreneurial orientation, characterized by a willingness to take calculated risks, is positively associated with the success of social ventures [33].…”
Section: Risk Management In Social Entrepreneurshipmentioning
confidence: 99%